Different Use of Cell Surface Glycosaminoglycans As Adherence Receptors to Corneal Cells by Gram Positive and Gram Negative Pathogens - García, Beatriz; Merayo-Lloves, Jesús; Rodríguez, David; Alcalde, Ignacio; García-Suárez, Olivia; Alfonso, José F.; Baamonde, Begoña; Fernández-Vega, Andrés; Vazquez, Fernando; Quirós, Luis M. (Frontiers in Cellular and Infection Microbiology, 2016)
The epithelium of the cornea is continuously exposed to pathogens, and adhesion to epithelial cells is regarded as an essential first step in bacterial pathogenesis. In this article, the involvement of glycosaminoglycans in the adhesion of various pathogenic bacteria to corneal epithelial cells is analyzed. All microorganisms use glycosaminoglycans as receptors, but arranged in different patterns depending on the Gram-type of the bacterium. The heparan sulfate chains of syndecans are the main receptors, though other molecular species also seem to be involved, particularly in Gram-negative bacteria. Adherence is inhibited differentially by peptides, including heparin binding sequences, indicating the participation of various groups of Gram-positive and -negative adhesins. The length of the saccharides produces a major effect, and low molecular weight chains inhibit the binding of Gram-negative microorganisms but increase the adherence of Gram-positives. Pathogen adhesion appears to occur preferentially through sulfated domains, and is very dependent on N- and 6-O-sulfation of the glucosamine residue and, to a lesser extent, 2-O sulfation of uronic acid. These data show the differential use of corneal receptors, which could facilitate the development of new anti-infective strategies.